Advances and tensions around access to therapeutic abortion in Costa Rica in the XXI century. - Preinfalk Fernández, María Luisa (2022)
Therapeutic abortion, a medical procedure that is practiced in order to protect the life or health of the pregnant woman because she is at risk due to complications with pregnancy, is directly linked to the exercise of human rights by women. This article systematizes some events that took place in Costa Rica in the period of 2000 - 2019, which have marked the course of the State’s actions regarding its obligation to ensure access to therapeutic abortion, with the aim of understanding the limitations that women have faced for their enjoyment, as well as to point out the progress made and the challenges that arise. The methodology used was the documentary review of texts produced in the country and national news material online. The results show that important steps have been taken - recently - with the approval of a technical norm that regulates this practice, but the panorama has been complex and marked by the interests of various social groups, with irreconcilable positions. The existence of a broad regulatory framework on Sexual and Reproductive Rights and the fact that therapeutic abortion is not criminalized by law, has not been sufficient to guarantee effective access to this procedure.